Innovative Development of Kazakhstan on The Basis of Triple Helix and Cluster Approach - Dnishev, Farkhat Musayevich; Alzhanova, Farida Gazizovna; Alibekova, Gulnaz Zhanatovna (Economy of Regions, 2015)
The aim of the research is to study the Triple Helix model feasibility in developing innovations and using cluster approach in Kazakhstan. There are possible points of the emergence of clusters in Kazakhstan. However, there are a lot of constraining factors. First of all, institutional and social factors: the culture of business, unfair competition, low trust of economic agents to each other and to power institutes, low psychological readiness for cooperation of the enterprises of various branches and regions, poor development of chambers of commerce, and industrial associations. For the time being, the majority of regions of Kazakhstan are characterized by a limited set of high technology industrial branches, and a sharp shortage of universities generating innovation and research institutes. The research results show that the open innovation model is realized in a limited scale that does not allow to export innovations into external markets, to participate in global technology chains and international research networks. At the same time, some interaction schemes and preconditions for the development of the Triple Helix model are emerging. However, in general, the innovation policy is not systemic; it does not unite actions in the sphere of science and technology, education, industry, and regional initiatives. As the result of the research, some policy implications are given. For the development of clusters in Kazakhstan, it is desirable to use such a way, as integration into global cluster networks. It is necessary to make use of foreign experience at which various specialized state agencies become participants of clusters. It is necessary to focus not only on science but also industry, which should play the central role in the innovation process.